Non Human Agents in the Legal Chain: The Social Biography of Narcotics Evidence in Indonesia - Bakharuddin Muhammad Syah; Rendy Ananta Prasetya (Journal of Innovative and Creativity (Joecy), 2026)
Illicit narcotics trafficking in Indonesia has reached alarming levels, with tens of thousands of cases and hundreds of tons of seized evidence each year. However, behind law enforcement efforts, narcotics evidence itself often becomes a new source of problems such as embezzlement, substitution, or “loss” involving rogue officers. This study aims to understand the social journey of narcotics evidence from seizure to destruction and to reveal its capacity as a non‑human agent actively shaping power relations within the criminal justice system. Using a qualitative approach with netnography, field observation, and in‑depth interviews with 9 key informants (investigators, logistics officers, supervisory officials, prosecutors), the data were analyzed using the frameworks of social biography (Appadurai, 1986; Kopytoff, 1986) and Actor‑Network Theory (Latour, 2005). The results show three critical phases: (1) the seizure phase as the ontological “birth” of evidence, fraught with tension between formal procedures and field practices; (2) the circulation phase within the logistics chain, creating “biographical stagnation” due to the contradiction between storage time limits (7‑14 days) and the duration of judicial processes (months), which becomes fertile ground for re‑commoditization; (3) the destruction phase as a ritual of state power and a theater of transparency that conceals leaks from previous phases. This study concludes that narcotics evidence is a non‑human agent actively shaping law enforcement practices, and that logistics governance reform requires not only procedural improvements but also digitization of the chain, revision of storage time regulations, and a cultural shift from a target‑oriented approach to process integrity